What Millennials Want: How to Optimize Their Work - Anandre Forastero; Bertina Sjabadhyni; Martina Dwi Mustika (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2018)
Abstract: It is known that it is quite difficult for companies to create a working environment that suits the characters of the Millennials, who are now undoubtedly make up the largest proportion of the workforce. This study aims to understand how job autonomy and boredom at work affect Millennials’ work engagement. Using non-probability sampling methods, 320 Millennial employees (19–37 years old) from various organizations (private and public organization) in Indonesia agreed to participate in this study. They filled in a questionnaire that measured the Utrecht Work Engagement Scale (UWES-9), Work Design Questionnaire (WDQ); and Workplace Boredom Scale. Data were analyzed using mediation analysis; and the results showed that boredom at work plays a significant role in mediating the relationship between job autonomy and employee engagement in Millennial employees. To conclude, job autonomy positively affects boredom levels of Millennial employees and low levels of boredom results in a higher employee engagement level.Abstrak: Dapat dipahami bahwa perusahaan kesulitan menciptakan lingkungan kerja yang sesuai bagi karyawan-karyawannya, khususnya karyawan Generasi Milenial yang merupakan pemain utama dalam dunia kerja. Tujuan penelitian ini adalah untuk melihat peran dari variabel-variabel yang diduga dapat mempengaruhi keterikatan kerja karyawan Generasi Milenial, yaitu kemandirian kerja dan kebosanan bekerja. Menggunakan metode non-probability sampling, 320 karyawan Generasi Milenial (19-37 tahun) dari berbagai organisasi di Indonesia (organisasi swasta dan negeri) bersedia berpartisipasi dalam penelitian ini. Mereka mengisi beberapa kuesioner, antara lain The Utrecht Work Engagement Scale (UWES-9) Work Design Questionnaire dan Workplace Boredom Scale. Analisis data yang digunakan adalah analisis mediasi; dan hasilnya menunjukkan bahwa kebosanan bekerja berperan signifikan dalam memediasi hubungan kemandiran kerja dan keterikatan kerja pada karyawan Generasi Milenial. Dapat disimpulkan bahwa kemandirian kerja dapat mempengaruhi kebosanan Generasi Milenial dalam bekerja dan rendahnya tingkat kebosanan dalam bekerja tersebut dapat mempengaruhi keterikatan kerja yang dimiliki.